Contemporary representation and imaginings of family, partnering and love among Black South Africans in Date My Family - Sithole, Candy (My University, 2019)
This study examines contemporary representation and imaginings of the black South African family structure in a popular reality television programme, Date My Family. Further categorised in the sub-genre of reality dating television, the programme is also a significant study of the ways in which reality television values intersect with discourses about family, romantic partnering and romantic love. These are the three main themes that have been identified in Date My Family, and are all fundamental and significant social practices that will be explored in a critical discussion of dynamics in black South African families. This study aims to outline the ways in which Date My Family displays contemporary understandings of black identity in relation to the family structure, as well as how the programme either imagines or renegotiates traditional conceptions of family, romantic partnering and romantic love. The study’s examination of its three main themes is informed by literature that serves an introductory and contextual function. Subsequently, I apply theories of identity, race and representation. Using discourse analysis to focus on the visual and verbal discourses, I show that the programme displays significant cultural relevance and a representation of the social circumstances in which it is produced. Date My Family portrays instances in which Western/ European traditions and conceptions of family, romantic partnering and romantic love have been continued in the African context, how some of these traditions and conceptions co-exist with those of Africa, and how these traditions and conceptions have been renegotiated. The structure of the black South African family seems to remain in its traditional form – the extended unit - and notions of female-headed households and an absence of fathers in the family remain topics of representation in the current, local context.
A thesis report submitted in partial fulfilment of the requirement for the degree of Master of Arts in Media Studies to the Faculty of Humanities, University of the Witwatersrand, 2019
Keywords: Point of view (Literature); Characters and characteristics in literature; Realism in literature